Strategi Pengembangan Usaha pada UMKM SHE’S Kitchen dengan Pendekatan SOAR Analysis dan Business Model Canvas (BMC) - Samira, Samira Anatha Syaza; Hadiyul Umam, M. Isnaini; Nur, Muhammad; Anwardi, Anwardi; Nofirza, Nofirza (Fakultas Teknik UMRI, 2023)
Data from the Ministry of Cooperative, UMKM, and UB (Large Enterprises )in 2018 shows an increase in the number of MSMEs with a proportion of 0,98% of 64.199.60,6 and in 2019 it has grown to 65.471.134. The increased number of MSMEs is the reason for the importance marketing strategies by MSMEs too penetrate more and more market competition. This study aims to analyze the internal and external factors that influence the business development strategy in MSME SHE’S Kitchen using the SOAR (Strength, Opportunities, Aspiration, and Result and BMC (Business Model Canvas) Methods of strategic planning that identifies and analyze a strength an opportunity so that it can produce aspirations, goals, strategies, and commitment to get the resulting desire by the company. In addition, this research also aims to provide BMC tourism as well as appropriate business transformation designs to be developed in SHE’S Kitchen UMKM. The result of this study obtained 10 alternative strategies based on SOAR matrix analysis and there were additional 6 BMC Strategy components, namely key resources, value propositions, customer relationships, customer segments, and revenue streams.